2015
DOI: 10.1016/j.physbeh.2015.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Chronic social defeat, but not restraint stress, alters bladder function in mice

Abstract: BACKGROUND Voiding disorders in humans, particularly in children are associated with increased incidence of behavioral issues as well as past history of childhood abuse. We hypothesized that creating stress in mice, utilizing either a chronic social defeat model (SD) or restraint stress in shallow water model (RSSW), would engender changes in bladder function, morphology, and behavior, thereby enabling us to study the resultant voiding dysfunction. METHODS For SD stress (14 days), C57BL/6 male mice were expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 39 publications
(52 reference statements)
4
20
0
Order By: Relevance
“…Exposure to physical or emotional stress produced a similar hormonal stress response in both groups, confirming that the mice used in this study were stressed when compared to controls. This is consistent with other experimental studies which assessed corticosterone levels in the social defeat model (Mann et al, 2015), as well as paired social defeat/witness trauma model (Sial et al, 2016;Li et al, 2018). Interestingly, while social defeat resulted in reduced urinary frequency, which supports previous reports of voiding dysfunction in this model (Chang et al, 2009;Mann et al, 2015), voiding was not altered in witness trauma mice despite a similar hormonal stress response.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Exposure to physical or emotional stress produced a similar hormonal stress response in both groups, confirming that the mice used in this study were stressed when compared to controls. This is consistent with other experimental studies which assessed corticosterone levels in the social defeat model (Mann et al, 2015), as well as paired social defeat/witness trauma model (Sial et al, 2016;Li et al, 2018). Interestingly, while social defeat resulted in reduced urinary frequency, which supports previous reports of voiding dysfunction in this model (Chang et al, 2009;Mann et al, 2015), voiding was not altered in witness trauma mice despite a similar hormonal stress response.…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with other experimental studies which assessed corticosterone levels in the social defeat model (Mann et al, 2015), as well as paired social defeat/witness trauma model (Sial et al, 2016;Li et al, 2018). Interestingly, while social defeat resulted in reduced urinary frequency, which supports previous reports of voiding dysfunction in this model (Chang et al, 2009;Mann et al, 2015), voiding was not altered in witness trauma mice despite a similar hormonal stress response. Mann et al (2015) similarly found that like witness trauma, chronic restraint stress did not alter bladder function, with similar voiding, bladder mass and bladder wall thickness compared to controls.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Indicators of stress : Previous research has shown that bladders from mice subjected to chronic stress undergo significant morphological change including hypertrophy and enhanced bladder-to-body weight ratios [ 20 ]. This index of stress was chosen because it demonstrates a physiological consequence to chronic stress.…”
Section: Methodsmentioning
confidence: 99%